UPAYA GURU DALAM MENINGKATKAN KEMAMPUAN MENULIS AWAL PADA ANAK KELOMPOK A DI RA SYIHABUDDIN LANDUNGSARI MALANG - Lutfia Sefta Bramastia; Khoirul Asfiyak; Ika Anggraheni (UNISMA, 2021)
This research discusses the teacher’s efforts in improving early writing skills in group A children. RA Syihabuddin is an institution under the auspices of the Al-Muhaimin Islamic Foundation which is located in Klandungan Hamlet, Landungsari Village, Dau District, Malang Regency. Research focus: how is the condition of children’s early writing ability? What are the strategy used by the teacher in improving early writing skills? What are the supporting and inhibiting factor in improving early writing skills?. The purpose of this research is to describe the condition of children’s early writing skills, describe the strategy used by teacher in improving early writing skills, describe supporting and inhibiting factor in improving early writing skills. The research was conducted at RA Syihabuddin Landungsari Malang. This type of research using a qualitative approach with the type of case study. The data sources used are primary and secondary. Collecting data using observation, interviews, and documentation. Data analysis using data reduction, data presentation, and conclusions. Data validation is a test of credibiliy, transferability, dependability and confirmability. The conclusion of this research is that the early condition of children in writing skills hasn’t been able, because early writing learning is first focused on alphabet introduction and alphabet understanding. And the strategy taken by the teacher in improving early writing skills uses the Montessori method with figure ground metal insets media to stimulate children’s early writing development.